Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Behavior Intention Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pelanggan PT.Lion Mentari Airlines - Resti Febrianis; Rose Rahmidani (Universitas Negeri Padang, 2022)
This study object to determine the effect of service quality and company image on behavior intention through satisfaction as an intervening variable for PT. Lion Mentari Airlines customers in the city of Padang. This type of research is causative research. The population in this study is the people of the city of Padang who have used the Lion Air airline. and the determination of the number of samples using the Cochran formula as many as 97 samples. The study used a purposive sampling technique. The data used were primary data types obtained through distributing questionnaires to the people of the city of Padang with predetermined criteria. The analytical method used is path analysis using SPSS 21.The results show that (1) service quality has a significant and positive effect on customer satisfaction, (2) company image has a significant and positive effect on customer satisfaction, (3) service quality has a significant and positive effect on behavior intention, (4) company image has a significant and positive effect. on behavior intention, (5) customer satisfaction has a significant and positive effect on behavior intention, (6) company image has a significant and positive effect on behavior intention through customer satisfaction as an intervening variable, (7) company image has a significant and positive effect on behavior intention through customer satisfaction as an intervention variable.Keywords : service quality, corporate image, customer satisfaction and behavior intention